What is (-i)^6? I need help please....

Answers

Answer 1
Answer:

Answer:

Step-by-step explanation:

-i= -i

-i^2= 1

-i^3= -i * 1 = -i

-i^4= 1 * (-1)  = -1

-i^5= -i

-i^6= 1

Answer 2
Answer:

Answer: -1

Step-by-step explanation:


Related Questions

For what values of x is the expression below defined?o A. 3 x s 1O B. -3 x 1O C. 3 x S-1
Evaluate the limit as x approaches 0 of (1 - x^(sin(x)))/(x*log(x))aka: Please include steps/explanation.
A basketball player makes 75% of her free throws. If she made 84 free throws this season, how many has she attempted?
The supplement of an angle is (180 - 2x)°. What is the measure of the angle (in terms of x)?
Susan drove an average speed of 30 miles per hour for the first 30 miles of a trip & then at a average speed of 60 miles/hr for the remaining 30 miles of the trip if she made no stops during the trip what was susan's avg speed in miles/hr for the entire trip.(A) 35(B) 40(C) 45(D) 50(E) 55

Please help ASAP!!!! Which expression is equivalent to

Answers

Answer:

First option on the list: (g^(15))/(8h^6)

Step-by-step explanation:

Use the distributive property of exponents to get rid of parentheses in the algebraic expression, evaluate the powers of the numerical factors, and finally, cancel common factors in numerator and denominator to arrive at the final answer:

((2g^5)^3)/((4h^2)^3) =(2^3g^(15))/(4^3h^6) =(8g^(15))/(64h^6) =(g^(15))/(8h^6)

Y^2+4x-6x-6y+5=0convert to standard form, find the vertex, focus, and the equation of the directrix line

Answers

I think it is :x= (Y^2)/(2)-3y+ (5)/(2).

But...not really sure



so first we group like terms
y^2+4x-6x-6y+5=0
y^2-6y-2x+5=0
so I suspect that you might have left out a x^2 but I'll try to solve it how it is

y^2-6y+5-2x=0
factor y^2-6y+5
what adds up to -6 and multiplies to get 5, -1 and -5
(y-5)(y-1)-2x=0
not sure how to procede but you could get it to this
(y-5)(y-1)=2x

Convert from feet to yards. 8,154feet=yards

Answers